HUBUNGAN PERSEPSI IBU HAMIL TERHADAP MUTU PELAYANAN ANC TERPADU DENGAN MINAT UNTUK KUNJUNGAN ULANG DI KLINIK BUNGA MERPATI KOTA PALU PROPINSI SULAWESI TENGAH - Hariyani, Tintin; Winarsih, Sri (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
In 2022, the K4 coverage of Bunga Merpati Clinic was 29.20%, a decrease of 25.3% compared to the K4 coverage in 2021 (54.5%). Total integrated ANC visits at Bunga Merpati clinic in 2022 decreased by 4.31% from 2021. This is due to an unfavorable perception that reduces the interest of pregnant women for repeat visits. The purpose of this study was to determine the relationship between pregnant women's perception of integrated ANC service quality with interest in repeat visits at Bunga Merpati Clinic in Palu. This research is quantitative research that uses a correlational research design with a cross sectional approach. The study population was 452 pregnant women. Sampling using probability simple random sampling technique. The sample number was 83 people. The research time is August 15 to 31, 2023. It consists of two variables, namely the independent variable (pregnant women's perception of the quality of integrated ANC services) and the dependent variable (interest in repeat visits). Data collection using questionnaires. Bivariate analysis using the chi-square test, with a meaning level of α = 5%. The results showed a relationship between pregnant women's perception of the quality of integrated ANC services with interest in repeat visits at Bunga Merpati Clinic in Palu city (p value = 0.001 or < 0.05). So based on the results of this study it can be concluded, that the better the perception of pregnant women will increase the interest of pregnant women for repeat visits.